Gotta Catch 'Em All: CCUS with endogenous technical change - Davide Bazzana; Nicola Comincioli; Camilla Gusperti; Denis Legrenzi; Massimiliano Rizzati; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2023)
Carbon Capture Utilization and Storage (CCUS) stands as a pivotal technology crucial for achieving the most ambitious climate objectives. Despite its prominent inclusion in energy mix projections, its current deployment falls short of the requisite level. Additionally, uncertainties surrounding future developments pose potential obstacles to its optimal diffusion. This study addresses two primary shortcomings that could impede the widespread adoption of CCUS. Firstly, it investigates how investments in CCUS technologies either compete with or complement other green research and development (R&D) activities. Secondly, it explores how the heterogeneity among different economies and the factors influencing the technology might lead to alternative configurations compared to the current trajectory. To address these issues, this study introduces CCUS into a regional Integrated Assessment Model (IAM) incorporating endogenous green R&D and heterogeneous cost functions. The model generates optimal pathways for both CCUS and green R&D, revealing a significant challenge: an insufficient valuation of R&D costs could potentially displace all investment in CCUS. Furthermore, the distribution of CCUS capital across regions by the end of the century necessitates substantial investments from regions with currently lower values, such as Europe and lowerincome countries. This research underscores the imperative need for policies that mitigate uncertainties surrounding future technologies and coordinate contemporary state investments. Such policies are essential for CCUS to attain the envisaged contributions to emission reduction targets.
Keywords: Q53; Q54; O32; 330; Carbon Capture Utilization and Storage (CCUS); Integrated Assessment Model (IAM); Green Research and Development (R&D); Climate Objectives; Technological Uncertainties; Regional Disparities; Emission Reduction Targets